The Local is Now Global: Building a Union Coalition in the International Transport and Logistics Sector - Barton, Ruth; Fairbrother, Peter (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2009)
SummaryTrade unions face a range of challenges in a global world. As trade, production and consumption relations change, unions have begun to consider how they organize and operate. The argument is that for trade unions to effectively challenge key aspects of these global relations, they must take steps to rebuild the way they organize and operate at local levels. The conditions for this step are a reflective and experienced leadership, opportunities for leaders to meet each other, and for activists to develop practices of solidarity, information exchange and union cooperation with each other. To explore these themes we study a proto-typical case of inter-union coalition building. Over the last four years, three remote and local transport unions, in Victoria, Australia have developed the Victorian Group of the International Transport Federation. In doing this, these unions are building on existing forms of organization and in the process, they are reforging their relations with each other so as to have the potential to challenge international employers.